Teaching Academic Writing for Publication in ELT: Bridging Students’ Classroom Writing to Scholarly Journal Publication - Evi Safitri Yulandari; Zihori Maulida; Ernaini Ernaini (JURNAL ASIMILASI PENDIDIKAN, 2026)
Academic writing has become an essential skill for university students, particularly in English Language Teaching (ELT), where publication in international journals is increasingly required. However, many English as a Foreign Language (EFL) students face significant challenges in transforming classroom writing into publishable academic articles. This study aims to explore the gap between classroom-based academic writing and publication-oriented writing and to propose an instructional framework to address this issue. This research employed a qualitative descriptive design involving students and lecturers in an ELT program. Data were collected through document analysis, classroom observation, and semi-structured interviews. The findings reveal that students encounter difficulties in linguistic accuracy, rhetorical organization, and understanding academic genre conventions. Additionally, traditional English for Academic Purposes (EAP) instruction is insufficient to prepare students for publication demands. The study proposes a publication-oriented academic writing model integrating genre-based instruction, process writing, and English for Research Publication Purposes (ERPP). The study concludes that academic writing instruction should shift from assignment-oriented practices to publication-oriented pedagogy to enhance students’ scholarly communication skills.